Morgagni Hernia Associated to Hiatal Hernia in An Octogenarian Patient, As a Cause of Abdominal Pain in Emergency (Revista de Medicina Clinica, 2021)
A 81 year old woman, with no relevant history, who came to Emergency for abdominal-cost pain of several days of evolution. Imaging tests revealed a large Morgagni diaphragmatic hernia associated with a large hiatal hernia. Morgagni's hernia is a rare entity, rarely found in elderly patients, as they are congenital diaphragmatic defects. Aditionally, this case is interesting due to the simultaneous presence of a large hiatal hernia, with few cases reported in the scientific literature.
Keywords: Morgagni Hernia; Hiatal Hernia; Octogenarian